The Correlations of Space Weather and Satellite Anomalies: RASAT - Kaplan, Mehmet; Hudaverdi, Murat (IEEE, 2013)
The main focus of this work is to review documented operational anomalies for Turkish Remote Sensing Satellite of RASAT, by assessing the identification and estimation of potential source of space weather agents. A statistical evaluation and correlation analysis were made using the log files from the launching up to date for RASAT. A number of severe solar flares have been reported during these operational periods by NAOO. The proton and electron fluxes are obtained from GOES-13 satellite archival data. The values are also simulated by Spenvis algorithm for comparison. RASAT was monitored regularly and all key parameters are logged in order to track operational values and alert if anything goes beyond the thresholds. Both tables are compared by superposed epoch analysis technique. Possible similarities or dissimilarities in fluctuations are interpreted for better understanding of space environment and its effects on electronics. We have detected four dates (29.11.2011, 04.02.2012, 12.07.2012 and 16.12.2012) in which RASAT performed severe corrections. Space weather conditions for the dates are checked by mainly focusing on the solar energetic particle flux variations. We try to understand underlying mechanisms of failure and anomalies. The results hopefully enable Turkish engineers, designers and scientists to efficiently eliminate the risk, minimize the cost, and optimize the design for future national space missions
Keywords: Satellite anomalies; RASAT; a correlation betweensatellite anomalies and space weather; solar energetic particles; Engineering